The Influence of Self-Leadership and Professional Competence on Teacher Performance - Asih Puji Hastuti; Ria Yuniawati; Siti Sutanti (Journal of Childhood Development, 2023)
This study aims to examine the effect of self-leadership and professional competence on teacher performance in Raudhatul Athfal's Temanggung District. This study used a purposive random sampling technique with a quantitative approach. The research subjects were 61 Raudhatul Athfal teachers in Temanggung Regency. The independent variables in this study are self-leadership and professional competence, while the dependent variable is teacher performance. Data was collected using a Google Form questionnaire on self-leadership, professional competence, and teacher performance indicators. The data were analyzed using Smart PLS 4. The results showed a positive and significant effect of self-leadership on teacher performance. Likewise, the analysis results of professional competency variables also positively and significantly influence teacher performance